Neonatal Tetanus, Yet Not Gone: Infectious Disease Hospital Experience - Ehsan, Amimul; Akter, Shaheen; Salam, Fatema (Journal of Enam Medical College, 2015)
Background: Although neonatal tetanus (NT) has been declared eliminated from Bangladesh in June 2008, it is not uncommon in Infectious Disease Hospital (IDH) in Dhaka. There are various presentations of NT cases and treatment practices also vary. Objective: This study was conducted to describe our experiences with NT at IDH outlining the clinical characteristics, maternal immunization and treatment outcome. Materials and Methods: Thirty neonates admitted with tetanus in IDH from March 2011 to December 2012 were observed prospectively to study risk factors, clinical features and outcomes during hospital stay. Results: Among 30 neonates with tetanus 80% were male. Eighty seven percent of these cases were delivered at home and 83% of mothers did not receive any dose of tetanus toxoid (TT). Fifty percent of the neonates were admitted within 35 days of age. Shidur (Vermillion) was applied to the cord stump in 23% neonates. Hot soak was applied to the umbilicus in 5 (17%) neonates. Presenting features were convulsion and/or stiffness or rigidity (93%), inability to suck (90%) and umbilical infection (70%). During hospital care multiple cardiac arrests developed in 86% neonates and apnea developed in 60% of the neonates. Treatment was given in pediatric ward. Case fatality rate was 50%. Conclusion: Risk factors observed in NT cases were maternal non-immunization, unhygienic delivery practices and application of substances in the umbilicus. Antenatal TT administration and universal immunization under school health program should be more emphasized to prevent NT. J Enam Med Col 2015; 5(3): 161-165